PERTANGGUNGJAWABAN PIDANA DALAM KASUS PEMBUNUHAN BERENCANA ATAS PERINTAH ATASAN - Muhamad Indra Aryan; Edi Saputra Hasibuan; Rabiah Al Adawiah (INTELIGENSIA MEDIA, 2023)
In this study, it aims to examine a criminal act of premeditated murder that occurs when a superior orders his members to commit a criminal act of premeditated murder that occurs in the State Civil Apparatus of the Republic of Indonesia. The research method used is the Normative research method by approaching the Legislation and the case approach. Types and sources of legal materials used use primary, secondary, tertiary materials by collecting legal materials. The theoretical framework in this research uses the theory of legal certainty, law enforcement, and the crime of murder. The conceptual framework in this study uses criminal liability, premeditated murder, and abuse of authority. The results obtained in the conclusions and suggestions of this research, conclude that the sentencing of this case is in accordance with legal certainty which refers to positive law, facts, reality. The judges of the district court have considered the defendant with several considerations so that the death penalty can be imposed by referring to juridical considerations and aggravating circumstances, and the Supreme Court judges have mitigated by focusing on mitigating and non-juridical matters. Considering that the District Court Panel and the Cassation Panel must weigh and decide the decision fairly, wisely, and impartially as stated in Law No. 48 of 2009 concerning Judicial Power.